Assessment at antiretroviral clinics during TB treatment reduces loss to follow-up among HIV-infected patients. - Dominique J Pepper; Suzaan Marais; Feriyl Bhaijee; Robert J Wilkinson; Virginia De Azevedo; Graeme Meintjes (PLoS ONE)
Setting A South African township clinic where loss to follow-up during TB treatment may prevent HIV-infected TB patients from receiving life-saving ART. Objective To determine factors associated with loss to follow-up during TB treatment. Design Regression analyses of a cohort of ART-eligible TB patients who commenced TB treatment and were followed for 24 weeks. Results Of 111 ART-eligible TB patients, 15 (14%) died in the ensuing 24 weeks. Of the remaining 96 TB patients, 11 (11%) were lost to follow-up. All TB patients lost to follow-up did not initiate ART. Of 85 TB patients in follow-up, 62 (73%) initiated ART 56 days after TB diagnosis (median, IQR 33-77 days) and 31 days after initial assessment at an ART clinic (median, IQR: 18-55 days). The median duration from TB diagnosis to initial assessment at an ART clinic was 19 days (IQR: 7-48 days). At 24 weeks, 6 of 85 (7%) TB patients who presented to an ART clinic for assessment were lost to follow-up, compared to 5 of 11 (45%) TB patients who did not present to an ART clinic for assessment. Logistic regression analysis (adjusted odds ratio = 0.1, 95% confidence interval [95% CI]: 0.03-0.66) and our Cox proportional hazards model (hazard ratio = 0.2, 95% CI: 0.04-0.68) confirmed that assessment at an ART clinic during TB treatment reduced loss to follow-up. Conclusion Assessment at antiretroviral clinics for HIV care by trained health-care providers reduces loss to follow-up among HIV-infected patients with TB.